Arabization Without Arabness: Cultural Hybridization and Islamic Identity in Post-New Order Indonesia - Ahmad Mujib; Abdul Aziz (Universitas Negeri Padang, 2026)
Since 1998, puritanical transnational Islamic movements have promoted “Arabized” practices in Indonesia, including Arab-style clothing, beards, veils, and Arabic greetings. These developments have prompted resistance from Nahdlatul Ulama (NU), which champions Islam Nusantara to preserve local cultural expressions of Islam. Existing studies remain focused on elite-level ideological oppositions, framing Arabization primarily as a homogenising threat to be countered by “local Islam” or on discursive constructions of “Arabness.” This article examines how “Arab” religious markers have infiltrated and become naturalised in local contexts during the Reformasi era, even in NU strongholds, despite opposition. It adopts a historical sociological approach that analyses long-term religious change, paying particular attention to everyday practices, power relations, and identity negotiation at the grassroots level. The study argues that Arab culture enriches local identities through selective indigenisation, thereby challenging binary threat-resistance narratives. Additionally, this research contributes to the historiography of Indonesian Islam beyond hegemonic binary discourses that contrast Islam Nusantara with Arabization or puritanical transnational influences. Instead, it traces how religious change and identity formation unfold through selective indigenisation and everyday hybridisation.